The Principle of Patrimonial Liability and Its Limitations - Bianca, Mirzia (2005)
Patrimonial liability refers to the duty of a person to respond with his or her assets in the event of a breach of an obligation. As the author points out, this principle has been explained by two theories. The first is the French theory of the personalisation of property, according to which property is an extension of a person's personality. The second is the German theory of 'assets for a purpose', which proposes that assets are defined not by a subject but by the purpose for which they are intended. In fact, both theories promote the principle of the indivisibility of property and therefore reject any limitation of property liability. However, the basis of this principle has evolved over time. Today, financial liability is based on an economic principle that seeks to achieve the values of profit and efficiency. Notwithstanding the above, the Italian Civil Code provides that limitations on property liability can only be established by law and not by private decisions. Although there is an ongoing debate to allow for greater flexibility through legislation, the principle of asset liability remains one that does not allow for exceptions.